Victorian Identities
XIII, 256 p.
Keywords: The Victorian period was one of enormous cultural diversity with places for figures as different as Alfred Tennyson and Oscar Wilde. Victorian Identities simultaneously celebrates that diversity whilst drawing out the connections between disparate voices. With essays on the 'Greats' of the period - Dickens, Tennyson, George Eliot, Wilkie Collins and Wilde - as well as on the less well-known sensation writer, Rhoda Broughton, and on the formation of children's voices in Victorian literature - the collection rejects narrow definitions of the period and its values, and exposes its texts to readings informed by contemporary literary theory.